The SACRED ART OF THE BEGINNING OF THE XXI CENTURY IN DECORATION OF THE TEMPLE ENVIRONMENT OF MARIA'S SPIRITUAL CENTRE IN ZARVANYTSIA - ДАЦЮК, Н. М.; НЕТРИБ'ЯК, М. М. (Art and Design, 2022)
The purpose of the article is to highlight the main directions and trends in the development of modern Ukrainian sacred art on the example of the interiors of the buildings of the Maria's Spiritual Centre in the village of Zarvanytsia, to identify artists who took part in decorating temples on the territory of the spiritual centre. The methodological basis of the study are a set of general scientific methods: description, interviews, comparisons, observations, a special methods: art analysis, field surveys, historical and comparative analysis. Results. The article highlights modern concepts of visual organization of the temple space on the example of sacred buildings of Maria's Spiritual Centre in the village of Zarvanytsia, Terebovlya district, Ternopil region. Also analyzes the formation of the stylistic orientation of wall paintings: from realistic trends in Ukrainian church painting to experiments with the stylization of iconic figures; introduction of modern iconography based on the traditions of Ukrainian art without violating established canons and traditions. Was considered the works of artists who took part in the decoration of churches on the territory of Maria's Spiritual Centre, namely: Volodymyr Svidersky, Yaroslav Kruk, Theodosius Buduykevych, Yevhen Ovcharyk, Peter Kukurudza and others. The scientific novelty of the study is that for the first time was analyzed and characterized the modern sacred art in the temples on the territory of Maria's Spiritual Centre, was identified the authors who joined the decoration of sacred buildings. All material is collected during field trips. Conclusions. The practical significance lies in the fact that materials presented in the article, their analysis and generalization can be used in the research on the development of Ukrainian sacred art of the early XXI century.